Pore water pressure responses of saturated sand and clay under undrained cyclic shearing - An,; Hiroshi,; Nhan,; Nhan,; Tien,; Thien, (Vietnam Journal of Earth Sciences, 2021)
In this study, changes in the pore water pressure were observed for saturated specimens of a loose fined-grain sand (Nam O sand) and a soft silty clay (Hue clay) subjected to undrained cyclic shearing with different testing conditions. The cyclic shear tests were run for relatively wide range of shear strain amplitude (g = 0.05%-2%), different cycle numbers (n = 10, 50, 150 and 200) and various shear directions (uni-direction and two-direction with phase difference of q = 0o, 45o and 90o). It is indicated from the experimental results that under the same cyclic shearing condition, the pore water pressure accumulation in Hue clay is at a slower rate, suggesting a higher cyclic shear resistance of Hue clay than that of Nam O sand. Liquefaction is reached easily in nominally 50% relative density specimens of Nam O sand when g ³ 0.4%, meanwhile soft specimen of Hue clay is not liquefied regardless of the cyclic shearing conditions used in this study. The threshold number of cycles for the pore water pressure generation generally decreases with g meanwhile, the threshold cumulative shear strain for such a property mostly approaches 0.1%. In addition, by using this new strain path parameter, it becomes more advantageous when evaluating the pore water pressure accumulation in Nam O sand and Hue clay subjected to undrained uni-directional and two-directional cyclic shears.